Post‐transcriptional regulation of PIAS3 expression by miR‐18a in malignant mesothelioma - Tian He; Karen McColl; Nneha Sakre; Yanwen Chen; Gary Wildey; Afshin Dowlati (Molecular Oncology, 2018)
Protein inhibitor of activated STAT3 (PIAS3) is an endogenous suppressor of signal transducer and activator of transcription 3 (STAT3) signaling. By directly interacting with phosphorylated STAT3, PIAS3 can block the downstream transcriptional activity of STAT3, which is hyper‐activated in various cancers. We previously reported that in malignant mesothelioma (MM), low PIAS3 expression is associated with increased STAT3 activation and correlates with poor patient survival, yet the regulatory mechanism(s) governing PIAS3 expression in MM remain unclear. Here, we demonstrate that PIAS3 protein expression does not correlate with its mRNA level in MM cell lines, indicating that PIAS3 expression is regulated at a post‐transcriptional level. Inhibition of proteasomal degradation with MG132 (10 μm) or bortezomib (1 μm), alone and in combination, did not increase PIAS3 protein levels; furthermore, inhibition of protein synthesis by cycloheximide treatment did not decrease PIAS3 levels within 48 h, suggesting that PIAS3 expression is not actively regulated at a post‐translational level. To determine whether miRNA (miRs) can translationally regulate PIAS3 expression, we combined miR microarray analysis with bioinformatic screening to identify candidate miRs, in MM cell lines with low PIAS3 expression, followed by luciferase reporter assays to validate miR regulation of the PIAS3 3′UTR. We identified miR‐18a as a suppressor of PIAS3 expression that is upregulated in MM cells and whose inhibition can increase PIAS3 expression and suppress STAT3 activity. Moreover, we showed that miR‐18a inhibition can decrease MM cell viability and that its expression is negatively correlated with MM patient survival. Taken together, these results suggest that targeting miR‐18a may have therapeutic benefit in MM.